The reasons for and implications of multilingualism in Une bouteille à la mer - Buckley, Thomas (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2013)
It is sometimes said that the only way to fully understand others is to learn their native language, suggesting that translation and interpretation are ultimately doomed to failure. Applying this principle to the conflict between the Israelis and the Palestinians, one would advise each of the two peoples to learn the other’s language in order to arrive at a mutual understanding. A film which explores this very situation, however, Une bouteille à la mer (Binisti, 2011), takes another tack, using first English, then French to overcome the misunderstanding, at least on an individual level. As a result, the spectator’s impression is that those who remain in their unilingual worlds of Hebrew and Arabic are stuck in ideological compartments that are reinforced by the walls of their respective languages. Instead of suggesting that in order to perceive and understand the Other’s real self one must learn his or her mother tongue, the film portrays foreign languages as rescue vehicles that can enable us to escape from intolerant, obscurantist worlds.